Transmogrification partition wall: TransWall / Chilter Mandau and Siti Akhtar Mahayuddin - Mandau, Chilter; Mahayuddin, Siti Akhtar (2023)
Partition walls are essential in building construction because they provide adaptability and seclusion in interior design. However, several challenges prevent its effective adoption. This project investigates new solutions to these difficulties while encouraging environmental sustainability, with a particular focus on compact dwellings with limited space. this study proposed an innovation, i.e., TransWall, built up from the existing partition wall designs through desktop research and simulations. TransWall stands out by enabling natural light to pass through, providing multipurpose use, and decreasing noise friction. These distinctive elements contribute to the creation of a comfortable and long-lasting living environment. With long-term growth goals in mind, this study seeks to overcome the limits of traditional partition walls and encourage the use of environmentally friendly products.